7ln(3x+10)=42

Simple and best practice solution for 7ln(3x+10)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7ln(3x+10)=42 equation:


Simplifying
7ln(3x + 10) = 42

Reorder the terms:
7ln(10 + 3x) = 42
(10 * 7ln + 3x * 7ln) = 42
(70ln + 21lnx) = 42

Solving
70ln + 21lnx = 42

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-42 + 70ln + 21lnx = 42 + -42

Combine like terms: 42 + -42 = 0
-42 + 70ln + 21lnx = 0

Factor out the Greatest Common Factor (GCF), '7'.
7(-6 + 10ln + 3lnx) = 0

Ignore the factor 7.

Subproblem 1

Set the factor '(-6 + 10ln + 3lnx)' equal to zero and attempt to solve: Simplifying -6 + 10ln + 3lnx = 0 Solving -6 + 10ln + 3lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 10ln + 6 + 3lnx = 0 + 6 Reorder the terms: -6 + 6 + 10ln + 3lnx = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 10ln + 3lnx = 0 + 6 10ln + 3lnx = 0 + 6 Combine like terms: 0 + 6 = 6 10ln + 3lnx = 6 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4x-5x=8x-9+11x | | 2*(7/2X) | | 3(3-x)=5(2x-7)+2 | | (-2/9)=4/a | | -9-6+3= | | 9(11-k)=9(x-5) | | r(6r+1)=12 | | 1/4x-1/6x=100 | | 59=-75 | | (5a-2b)+(3a-4b)=0 | | 8(w+3)+4=-7w+11 | | 90x+50=100x | | 4(5-x)=-4.9+2.1(6x) | | 5(x+1)-2(x-1)=12 | | -(v+9)+7=-7v-12 | | -15x+8=7-15x | | 9p+7=6+3(p-1) | | x=x^2+6x+15 | | 9q+7=6+3(p-1) | | 3x+7=-2x-23 | | Ln(3)+ln(2)=ln(x) | | -7(s+10)+11=-5s-6 | | 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) |

Equations solver categories